Evaluation of light backscattering by zinc oxide nanorods on fiber end of silica optical fiber - Lokman, M.Q.; Rahim, H.R.A.; Yasin, M.; Jusoh, Z.; Harun, Sulaiman Wadi (INOE, 2016)
Light backscattering by Zinc Oxide (ZnO) nanorods at different growth duration is investigated. Synthesis of ZnO nanorods was done using hydrothermal techniques on the end of silica optical fiber (SOF), the growth duration of nanorods is varied at 4, 6 and 8 hrs. Optical and physical characterization was accomplished to validate the light backscattering and morphology of ZnO. Optical characterization was performed by measuring the output power of the backscattered light, the result indicates that 8 hrs growth duration is optimum to achieve the highest backscattering. The sample with the optimum growth time was analyzed using the field emission scanning electron microscopy (FESEM) image and electron dispersive spectrum (EDS) result. Both results confirmed the presence of ZnO on the end of silica fiber.